Nitzschia gobbii sp. nov. (Bacillariophyceae): a common but overlooked planktonic diatom species from the northwestern Adriatic Sea. Issue 6 (2nd November 2021) - Giulietti, Sonia; Totti, Cecilia; Romagnoli, Tiziana; Siracusa, Melania; Bacchiocchi, Simone; Accoroni, Stefano
ABSTRACT: Planktonic diatoms of the family Bacillariaceae, including Nitzschia spp, Pseudo-nitzschia spp and Cylindrotheca closterium, are common and often highly abundant in the Adriatic Sea. During the 30 years of phytoplankton monitoring at the coastal site of the LTER Senigallia-Susak transect, a nitzschioid diatom with morphology matching that of Nitzschia section Nitzschiella (dilated central portion and two long rostra) was frequently observed. In this study, we describe this new species as Nitzschia gobbii sp. nov., combining morphological (transmission electron microscopy and scanning electron microscopy) and molecular (LSU and ITS rDNA) data. The morphology of Nitzschia gobbii makes it easy to confuse with other common species in the Adriatic Sea ( Cylindrotheca closterium and Pseudo-nitzschia galaxiae ). The partial LSU rDNA sequences of strains of Nitzschia gobbii sp. nov. were resolved in a well-supported clade. In this area, this species has been mainly recorded in spring-summer with a maximum abundance of 3.2 × 10 6 cells l –1 . None of the tested Nitzschia gobbii strains produced domoic acid in detectable amounts.